Restoration of the Bojongsoang Lake Oxbow Function in Citarum River - Prasetya, Adhita; Komarudin, Udin; Martoni, (International Journal of Psychosocial Rehabilitation, 2020)
Citarum River as an infrastructure has a function to distribute water but has several limitations, one of which is the ability of the river to accommodate rainwater that occurs in the watershed. River alignment activities undertaken by the government in the 80's produced an abundant oxbow lake in the Citarum river. And based on data from Balai Besar Wilayah Sungai Citarum, it is estimated that 1.5 million m3 of water can be accommodated by an oxbow lake, or equivalent to the construction of 1 dam. Lack of maintenance and concern of stakeholders resulted in the oxbow lake not being able to function as expected. The objective of this paper is to present the results of oxbow lake dredging activities as an effort to reduce the impact of floods in Upper Citarum and utilization of oxbow lake for various purposes, such as education, recreation, protection of state assets, and conservation.